Pengembangan Model Pembentukan Sel dengan Kriteria Majemuk - Hidayat, Trifenaus Prabu (Metris: Jurnal Sains dan Teknologi, 2016)
Stages of designing the layout of the manufacturing cell involves three steps: (1) the cells formation, (2) designing the layout of the intracellular and (3) designing the layout of intercellular. This study made a model of cell formation. At this stage of cell formation, the criteria to be considered are the cost of an additional investment of machinery, material handling costs intracellular, intercellular material handling costs, cost of work in process and penalty fees under the machine utilization. Intracellular layout design stage, the criteria to be considered is the cost of work-in-process. While the design stage layout intercellular consider the cost of work-in-process. The performance of the layout of the cells was evaluated using a numerical example.